A Rare Disease in Adult: Langerhans Cell Histiocytosis - Berber, Ilhami (World J Oncol, 2013)
Langerhans cell histiocytosis is a rare histiocytic disorder and has been diagnosed in all age groups, but is most common in children. This disease is very rare in adults. We presented a patient who was 62 years old man diagnosed langerhans cell histiocytosis.